Diaspora Hadrami di Asia Tenggara - Subhan, Arief (Studia Islamika, 2002)
This book under review is basically in the same line as the above mentioned book it focus to the roles the Hadrami held in the destination countries of their diaspora. The difference lies in the fact that this book concentrated its discussion to the Hadrami diaspora in Southeast Asia. This present book, edited by Huub de Jong and Nico Kaptein, originates from a workshop held in Leiden (1997), "The Arab in Southeast Asia (1870-1990)", which was organized by the Koninklijk Instituut voor Taal-Land- en Volkenkunde (KITLV) in conjunction with the International Institute for Asian Studies (IIAS), Leiden. All papers in this book, except the work by Ahmad lbrahim Abu Shouk, come from those presented in the workshop. Taking Southeast Asia as its main focus, this book contributed to the understanding of a rather neglected aspect of the Hadrami diaspora in the world.DOI: 10.15408/sdi.v9i3.663